1994
DOI: 10.1183/09031936.94.07071227
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant activity of bronchoalveolar lavage fluids taken from the site of tuberculous lesions

Abstract: P Pr ro oc co oa ag gu ul la an nt t a ac ct ti iv vi it ty y o of f b br ro on nc ch ho oa al lv ve eo ol la ar r l la av va ag ge e f fl lu ui id ds s t ta ak ke en n f fr ro om m t th he e s si it te e o of f t tu ub be er rc cu ul lo ou us s l le es si io on ns s ABSTRACT: We wanted to determine the procoagulant activity (PCA) of bronchoalveolar lavage fluids, in order to understand the macrophage-mediated lung injury at the site of tuberculous lesion. Alveolar lavage fluids taken from the site of a lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…At 9 wk, BAL cell clustering accompanied cytolysis, and this feature was markedly greater in Nrf2 -/- mice compared to Nrf2 +/+ mice (Figure S1). This observation is assumed to be associated with excess viscous secretion such as mucus as suggested by aggregation of cells with secreted mucus in Alcian Blue (pH 2.5)/periodic acid-Schiff (AB/PAS)-stained lungs (Figure S1), or by procoagulant activity due to fibrin deposition in mononuclear phagocytes which occurs during lung inflammation [16], [17]. Infiltrated neutrophils were obvious but not quantifiable due to extensive clustering and lysis of BAL cells in Nrf2 -/- mice; consistent with this observation, neutrophil myeloperoxidase (MPO) activity was significantly higher in Nrf2 -/- mice than in Nrf2 +/+ mice treated with urethane (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…At 9 wk, BAL cell clustering accompanied cytolysis, and this feature was markedly greater in Nrf2 -/- mice compared to Nrf2 +/+ mice (Figure S1). This observation is assumed to be associated with excess viscous secretion such as mucus as suggested by aggregation of cells with secreted mucus in Alcian Blue (pH 2.5)/periodic acid-Schiff (AB/PAS)-stained lungs (Figure S1), or by procoagulant activity due to fibrin deposition in mononuclear phagocytes which occurs during lung inflammation [16], [17]. Infiltrated neutrophils were obvious but not quantifiable due to extensive clustering and lysis of BAL cells in Nrf2 -/- mice; consistent with this observation, neutrophil myeloperoxidase (MPO) activity was significantly higher in Nrf2 -/- mice than in Nrf2 +/+ mice treated with urethane (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance, a previous study also reported a trend towards enhanced procoagulant activity in BALF of patients with lung TB. 34 Taken together it is unlikely that local haemostatic alterations are the driving force behind the hypercoagulable state at the systemic level in patients with lung TB.…”
Section: Discussionmentioning
confidence: 99%
“…Among other clinical presentations, increasing evidence indicates the presence of hematologic abnormalities, particularly disseminated intravascular coagulation (DIC) and deep-vein thrombosis (DVT), in TB patients [2] – [4] . The hemostatic and inflammatory changes in TB can result in a hypercoagulable state [3] , [5] . The prevalence of venous thromboembolism ranges from 0.6% to 3% in TB patients [6] and clinical reports emphasize that patients with severe pulmonary TB are at risk of developing thromboembolic events [7] .…”
Section: Introductionmentioning
confidence: 99%